Content analysis of online news portal:issues and challenges - Ahmad, Zeti Azreen; Buyong, Mazni (Faculty of Social Sciences and Humanities, UKM, 2017)
Content analysis is a well-established research technique that has been used to examine myriad type of texts including political messages. In the field of media research, it is a popular method to examine media contents systematically. At present, researchers continue to apply the established content analysis technique that was originally designed for traditional media on Web-based media and social media. However, the application of an established content analysis in the digital environment was claimed to be problematic by many scholars in view of the liquidity of online content. The paper is based on an empirical work conducted during the general election campaign period in 2013 that examined type of political news reported in a news portal; Malaysiakini. We argued that analysing online news using content analysis requires a different procedure especially in terms of capturing the ever changing content of the news portal. The paper also highlighted issues and challenges of adopting established content analysis technique on online news. Keywords: content analysis, Malaysiakini, method, liquidity, online news, political news